Improving the Welfare of SMEs through Islamic Bank Financing - Sri Rokhlinasari; Ridwan Widagdo (IAIN Syekh Nurjati Cirebon, 2019)
Micro, small and medium enterprises (MSMEs) are one of the efforts to advance the Indonesian economy, especially in the city of Cirebon. Business and economic ventures that are run are able to create and expand employment opportunities to encourage economic growth, strive to help increase community income and realize national stability. For this reason, the role of banks, especially Islamic banking, is highly needed in order to encourage MSMEs to become even more advanced. This study uses a qualitative approach to data collection techniques through: interviews with Islamic banks and MSMEs in Cirebon, as well as observation, and documentation. The validity of the data is processed by triangulation, which is a data validity checking technique that utilizes something else outside the data for checking or comparison purposes. The results of the study explained that the financing procedures carried out by the Islamic banking are not complicated and show an increase in business that can be seen from the increasing number of customers, growing businesses and the addition of employees. The results show that the role of banks in terms of distribution needs to be intensified even more because it has been proven that MSMEs are stronger in dealing with the world economy and supporting the national economy.Key words: Islamic banking, Sharia financing, MSMEs,